To Analyse the Perceived Attitude of Bankmed Medical Scheme Members, Age 18-30 Years, Toward the Medical Aid within the Framework of the Censydiam Model. - Bam, Michelle (The IIE, 2015)
Following the outcome of the Bankmed quantitative Member Satisfaction and Loyalty survey where the member segment aged 18 – 30 years was identified as “Potentially Lost”. Potentially lost members are characterised by poor attitude and behaviour in that there is a small likelihood that they would continue using your product and service should they be able to choose an alternative. In addition your brand is also not their preferred brand (Ipsos Loyalty 2015). It was determined that research into this segment be conducted in order to ascertain how best to favourably position the Bankmed brand and brand offering in the minds of this target audience. The research objective is to analyse the perceived attitude of the Bankmed medical scheme members, age 18-30 years, toward the medical aid within the framework of the Censydiam Model. The research will focus on an understanding of these members’ needs and motivations and provide direction as to how to connect the Bankmed brand with these deeper human motivations and ultimately ensure the brand resonates with this segment. The Censydiam Model research framework will be utilised as it seeks to uncover core human motivations associated with a specific category (in this case medical aid), thereby growing brands by recommending how they can connect to these deeper human motivations. To address the research objectives two 3-hour Censydiam qualitative focus groups, semi-structured conversational interviews, has been conducted with males and females, age 18 – 30 years, separately within a targeted accessible and most appropriate population given the complexity of the research problem. This research has shown that a one-size-fits-all approach is not likely to be successful with the younger segment in Bankmed. The segment feels disempowered and disengaged from the category, and is unable to see return on investment in their health, particularly given that they are contributing monthly, which compromises their take-home salary, but making minimal use of medical facilities. Part of their disempowerment lies in the all-inclusive communications distributed by Bankmed, which presents as a one-way communication that puts members in a subordinate position, whereas young members respond better to a dialogue between Michelle Bam_PHBL_student no: 12016236 (part time) Page 10 equals. It was also seen that changes in life stage, specifically the arrival of dependants, result in a change in the motivational space underlying members’ approach to healthcare cover from a ‘me-orientation’ to an ‘us-orientation,’ which is where the core motivational space for the category is to be found. The core motivational spaces for the medical aid category have been identified on the Censydiam model as Security (segment name “Sanctuary Seekers”) and Belonging (segment name “Carers”). Sanctuary Seekers want to know that they are covered for every medical eventuality, and want to feel reassured that their healthcare cover provider has the track record and capabilities to guarantee this cover. The Carers need to know that all their loved ones are covered by their healthcare cover, and that they are receiving similar care from their provider. Currently Bankmed is positioned in the Sanctuary Seeker segment but it is advised to investigate the feasibility of relocating itself in the Carer segment The primary audience for this research is the Bankmed CEO and the Bankmed Brand Council, and the key message to this audience is to reposition the brand as a brand that does not merely care for members (enable them to take care of their primary medical needs), but cares about them – positioning Bankmed as a co-traveller on the journey to achieve and maintain health, thereby optimising oneself in all spheres of life. The secondary audience for this research is the brand team, and the key message to this audience is to reconsider the channel, tone and content of communications to reinforce the relationship between provider and member as a collaboration rather than an enablement; it would be advisable that channels include social media platforms in order to cue relevance, and that messaging be personalised and targeted rather than over-generalised. The results of the research will influence the strategic direction of how to position the Bankmed value offering and communication content and channels to optimise brand resonance and equity.
Keywords: Attitudes; Consumers; Consumer Behaviour; Medical Aid; Branding; Consumer Motivation; Focus Groups; Communication